2014
DOI: 10.1007/s00284-014-0659-8
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Methanosarcinales Phylotypes and Depth-Wise Distribution of Methanogenic Community in Fresh Water Sediments of Sitka Stream from Czech Republic

Abstract: The variation in the diversity of methanogens in sediment depths from Sitka stream was studied by constructing a 16S rRNA gene library using methanogen-specific primers and a denaturing gradient gel electrophoresis (DGGE)-based approach. A total of nine different phylotypes from the 16S rRNA library were obtained, and all of them were clustered within the order Methanosarcinales. These nine phylotypes likely represent nine new species and at least 5-6 new genera. Similarly, DGGE analysis revealed an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Our previous study conducted on the Sitka stream also revealed phylotypes from the orders Methanosarcinales, Methanomicrobiales, and Methanobacteriales (Brablcova et al., ; Buriankova et al., ; Chaudhary et al., ). A community profiling using denaturing gradient gel electrophoresis DGGE presented by Brablcova et al., () showed nine bands for Methanosarcinales, one band for Methanomicrobiales, and one band for Methanocellaceae.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our previous study conducted on the Sitka stream also revealed phylotypes from the orders Methanosarcinales, Methanomicrobiales, and Methanobacteriales (Brablcova et al., ; Buriankova et al., ; Chaudhary et al., ). A community profiling using denaturing gradient gel electrophoresis DGGE presented by Brablcova et al., () showed nine bands for Methanosarcinales, one band for Methanomicrobiales, and one band for Methanocellaceae.…”
Section: Discussionmentioning
confidence: 90%
“…Currently, there are seven orders of methanogenic archaea described in literature (Borrel et al., , ; Lang et al., ). However, our previous study conducted on the Sitka stream (Location IV) revealed only three major methanogenic groups using molecular techniques (denaturing gradient gel electrophoresis and cloning): Methanosarcinales, Methanomicrobiales, and Methanobacteriales (Brablcova, Buriankova, Badurova, Chaudhary, & Rulik, ; Buriankova et al., ; Chaudhary et al., ). Hence, we focused our attempts to verify these results with molecular fingerprinting and qPCR to cover these three groups; in addition, we want to expand our knowledge by comparing two different sites and two sampling occasions..…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This can be reduced if combined with an oriented cloning and/or a fingerprinting technique (Mihajlovski et al 2008), which leads to an easiest selection of clones (based on restriction fragment length polymorphism (RFLP) for example). To our knowledge, there are few reports of the application of denaturing gradient gel electrophoresis (DGGE)/temporal temperature gel electrophoresis (TTGE) (Muyzer 1999) in studying human gut archaea or methanogens specifically (Abell et al 2006;Nam et al 2008), despite having already been extensively used for other environments (see for example Nakamura et al 2009;Chaudhary et al 2014). One major limitation of this technique relies on its inability to differentiate minor base pair differences in two sequences and thus may result in single band for different microbial strains.…”
Section: Cloning and Fingerprinting Techniquesmentioning
confidence: 97%
“…While the study of stream CO 2 biogeochemistry has received considerable attention over the last decade, the biogeochemistry of CH 4 (Crawford et al, 2014;Trimmer et al, 2015;Stanley et al, 2016) and specifically the microbial ecology of aerobic CH 4 oxidizing bacteria (MOB) in streams remains poorly understood (Trimmer et al, 2015(Trimmer et al, , 2010Stanley et al, 2016). Streams outgas substantial amounts of CH 4 originating from groundwater and methanogenesis within the streambed (Chaudhary et al, 2014;Stanley et al, 2016). Globally, streams and rivers may emit 26.8 Tg CH 4 per year, which is similar to the combined contribution of other natural CH 4 sources such as wildfires, termites, CH 4 hydrates, and permafrost (Stanley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%